Short and long-term evaluation of the impact of proton minibeam radiation therapy on motor, emotional and cognitive functions - Charlotte Lamirault (Nature Portfolio, 2020)
Abstract Radiotherapy (RT) is one of the most frequently used methods for cancer treatment. Despite remarkable advancements in RT techniquesthe treatment of radioresistant tumours (i.e. high-grade gliomas) is not yet satisfactory. Finding novel approaches less damaging for normal tissues is of utmost importance. This would make it possible to increase the dose applied to tumours, resulting in an improvement in the cure rate. Along this line, proton minibeam radiation therapy (pMBRT) is a novel strategy that allows the spatial modulation of the dose, leading to minimal damage to brain structures compared to a high dose (25 Gy in one fraction) of standard proton therapy (PT). The aim of the present study was to evaluate whether pMBRT also preserves important cerebral functions. Comprehensive longitudinal behavioural studies were performed in irradiated (peak dose of 57 Gy in one fraction) and control rats to evaluate the impact of pMBRT on motor function (motor coordination, muscular tonus, and locomotor activity), emotional function (anxiety, fear, motivation, and impulsivity), and cognitive function (learning, memory, temporal processing, and decision making). The evaluations, which were conducted over a period of 10 months, showed no significant motor or emotional dysfunction in pMBRT-irradiated rats compared with control animals. Concerning cognitive functions, similar performance was observed between the groups, although some slight learning delays might be present in some of the tests in the long term after irradiation. This study shows the minimal impact of pMBRT on the normal brain at the functional level.